Hemorrhagic encephalopathies and myelopathies in dogs and cats: a focus on classification - Santifort, Koen M.; Platt, Simon (Frontiers in Veterinary Science, 2024)
The prevalence of hemorrhagic diseases of the central nervous system of dogs and cats is low compared to other diseases such as neoplasia and inflammation. However, the clinical consequences can be devastating. Several etiological and localization-based classification systems have been reported for intracerebral and spinal cord hemorrhage or hematomyelia in humans but similar systems do not exist in veterinary medicine. The authors propose an etiologic classification system for both intraparenchymal hemorrhagic encephalopathy and myelopathy following a review of the literature detailing the presentation, diagnosis, therapy, and prognosis of these diseases. A summary of the investigative and therapeutic approach to these cases is also provided.